Effect of temperature change on bacterial virulence - Chen, Zihan (2018)
Abiotic factors such as temperature can influence the evolution of the pathogens, but empirical evidence on this is very scarce. The pathogen Serratia marcescens, which had evolved under three different temperature treatments for 1 month, and ancestor (ATCC 13880) of the evolved strains, were tested for their virulence in Galleria mellonella- wax moth. Bacteria injected larvae were incubated in two different temperatures to explore phenotypic plasticity in virulence. The mortality of the hosts was recorded and analysed. Survival analysis with linear mixed-effects model in R revealed that temperature change affected the bacteria virulence. Ancestor and those strains that had evolved in constantly high 38°C temperature were found to exhibit high virulence whereas strains evolved in benign 31°C, constant or fluctuating (daily fluctuations between 24-38°C) were found to have attenuated virulence. Whole genome sequencing of evolved strains n=28 revealed putative and new virulence factors. My results show that high temperatures are able to maintain and select for genes increasing virulence. If my result reflects things in the wild and also in other pathogens results mean problems associated with increasing mean temperatures due to global change .